Ramy finansowe Unii Europejskiej na lata 2007-2013 a cele Strategii lizbońskiej - Cybulski, Leszek (The EU's Financial Framework for the Period 2007-2013 and the Lisbon Strategy Goals, 2007)
Community's strategy of the economic development was adopted on the EU meeting in March 2000. It puts forward ambitious development goals, which should lead to the decrease of the gap between the EU and the USA. The strategy focuses mainly on augmenting the competitiveness through liberalization and deregulation, technological progress and diffusion of the high technology, improving of educational quality and deep reforms of labour markets. The time of passing the strategy was not correlated with the 2000-2006 financial programming period, where funds were already earmarked. The main conclusion of the paper is that modernization of the European economies was seen in projects of the new financial framework for the period 2007-2013. But because of decreasing tendency in amount of the European budget these expenditures were exceptionally cut. Therefore, modernization of the European economy will not find sufficient budgetary support in the period 2007-2013.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 75-94